Preparation of a novel polysulfone membrane by incorporated with carbon dots grafted silica from rice husk for dye removal. (April 2021) - Heng, Zeng Wei; Tan, Yee Yen; Chong, Woon Chan; Mahmoudi, Ebrahim; Mohammad, Abdul Wahab; Teoh, Hui Chieh; Sim, Lan Ching; Koo, Chai Hoon
Graphical abstract: Highlights: Carbon dots was derived from rice husk using hydrothermal method. Carbon dots enhanced the negative surface charge of the SiO2 as membrane additive. CD/SiO2 composite was embedded into polymeric membrane for properties improvement. CD/SiO2 composite improved the membrane permeability and rejection ability. Abstract: This study demonstrated the modification of polysulfone (PSf) membrane by incorporating carbon dots (CDs) and silica (SiO2 ) as additives for membrane's permeability and dye rejection enhancement. Both the CDs and SiO2 were synthesized from rice husk and the carbon dots were impregnated on SiO2 to form CD/SiO2 composite through a hydrothermal synthesis reaction. The impregnation of CDs had shown increment of hydrophilic functional groups with negative surface charge on the SiO2 . A series of CD/SiO2 composite embedded ultrafiltration (UF) membranes was developed. Results revealed that the CD/SiO2 additive was endowed with enhanced membrane properties in terms of pore size, pore distribution, hydrophilicity and negative surface charge. All the modified membranes demonstrated higher permeability and dye rejection. Among the membranes, 1.0 wt% of CD/SiO2 loading showed excellent pure water permeability increment of 111 % due to improved membrane hydrophilicity and enlargement of membrane pores. Notably, the 2.5 wt% of CD/SiO2 membrane showed the highest dye removal of 50.54 % compared to pure PSf membrane of 14.52 % albeit it had similar permeability as the pure PSf membrane. This study had demonstrated a circular economy approach in turning rice husk biomass into useful additives for membrane nanotechnology application.